2012
DOI: 10.1016/j.mar.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Why do employees take more initiatives to improve their performance after co-developing performance measures? A field study

Abstract: Performance measurements may stimulate employee initiatives to improve operational performance, especially when they themselves participate in the development of their own departmental performance measures. Using the theory of planned behavior, we examine why this occurs in a beverage manufacturing company where we helped bottling line maintenance technicians develop measures about the results of their own work. Our analyses are based on qualitative data gathered at 156 meetings, 34 semi-structured interviews,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
15

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 108 publications
5
88
0
15
Order By: Relevance
“…PM systems should be designed and implemented on the basis of both their formal ability to represent organizational aims and objectives, and their influence on stakeholders (Micheli and Mari, 2014). For NFPs that are engaging with new partners on performance goals, or for funders 28 who require performance reports from their grantees, using PM to reconcile perspectives on intended performance ahead of launch could prove more effective for supporting the alignment and achievement of objectives in the long term than merely imposing a predetermined set of measures (Groen et al, 2012;Millar and Hall, 2013). Furthermore, by understanding and embedding the institutional logics of front-line workers into PM practices, managers of NFPs can better support the achievement of social welfare objectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PM systems should be designed and implemented on the basis of both their formal ability to represent organizational aims and objectives, and their influence on stakeholders (Micheli and Mari, 2014). For NFPs that are engaging with new partners on performance goals, or for funders 28 who require performance reports from their grantees, using PM to reconcile perspectives on intended performance ahead of launch could prove more effective for supporting the alignment and achievement of objectives in the long term than merely imposing a predetermined set of measures (Groen et al, 2012;Millar and Hall, 2013). Furthermore, by understanding and embedding the institutional logics of front-line workers into PM practices, managers of NFPs can better support the achievement of social welfare objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Bourne et al (2013) uncovered intimate links between human resource management practices, PM, and their cumulative effects on stakeholders' motivations, efforts, and abilities to contribute to overall organizational performance. Groen et al (2012) concluded that for employees to be engaged in performance improvement initiatives, they need to be involved in the design of measures related to such initiatives. In sum, these studies suggest that PM processes and practices are inextricably related to behaviors, as individuals' interpretations of performance measures influence their actions, which, ultimately, affect organizational performance.…”
Section: Performance Measurementmentioning
confidence: 99%
“…This is clearly evident in both Argyris (1953) andHopwood (1973) where a diverse range of psychological reactions to budgeting and performance evaluation were observed and analysed. More recently, Groen et al (2012) use a field study to examine the motivational, social and cognitive processes generated from employee participation in the development of a performance measurement system. In particular, they use the theory of planned behaviour to understand how and why participation in the development of a performance measurement system is linked to employee initiative through different psychological processes (attitudes, felt social pressure, and capabilities).…”
Section: Bringing the Field Back Inmentioning
confidence: 99%
“…The use of a PMS within a PSF often causes unproductive side effects such as diminished autonomy, flexibility and employee professionalism (Bernard, 2008;Kärreman et al, 2002). We build on the ideas of enabling formalization (Adler & Borys, 1996;Ahrens & Chapman, 2004) and argue a PMS purposively developed for a small PSF should be enabling, facilitating employees rather than just their managers (Groen et al, 2012;Robson, 2005;Wouters and Wilderom, 2008). Such an enabling PMS gives employees guidance in making decisions in line with the strategy of the organization and preserves their autonomy at the same time, which is important for professional service employees (Von Nordenflycht, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Such an enabling PMS gives employees guidance in making decisions in line with the strategy of the organization and preserves their autonomy at the same time, which is important for professional service employees (Von Nordenflycht, 2010). A dedicated enabling PMS can be built by involving employees in the development and implementation process (Bernard, 2008;Groen et al, 2012;Wouters and Wilderom, 2008). In the same vein, Blili and Raymond (1998) recommend involving users when implementing information systems in small firms.…”
Section: Introductionmentioning
confidence: 99%